Modelling Domestic Tourism Demand in Australia A Dynamic Panel Data Approach - Ghialy Yap (Universitas Islam Indonesia, 2009)
Domestic tourism in Australia generates about 74% of total tourism revenue. Given that, thispaper examines whether changes in Australian households’ income and the prices of domestictravel can influence the demand for domestic travel. It reveals some notable results. First,Australian households will not choose to travel domestically when there is an increase inhousehold income. Second, an increase in the current prices of domestic travel can cause thedemand for domestic trips to fall in the next one or two quarters ahead. Finally, the coefficientsfor lagged dependent variables are negative, indicating perhaps, that trips are madeon a periodic basis.Keywords: domestic tourism, Australia, households’ income, domestic travel